Analisis Efisiensi Bank Pembiayaan Rakyat Syariah (BPRS) Di Surakarta Menggunakan Data Evelopment Analysis (DEA) Periode 2015 - Adi Nugroho, Taufiq; , Ir. Maulidyah Indira MS (2016)
This research aims to determine and analyze the efficiency of Islamic Rural Bank (BPRS) in Surakarta/Solo. Using Data Evelopment Analysis (DEA) with input oriented approach in the periode 2015. By using secondary data obtained for the quarterly financial statement 4 Islamic Rural Bank (BPRS) in Surakarta/Solo which has been published on the official website of the Otoritas Jasa Keuangan (OJK) is www.ojk.go.id . Based on calculations by software DEAP version 2.0, in the first quarter there were 4 BPRS efficient. In the second quarter ther were 4 BPRS efficient. In the third quarter there were 2 BPRS efficient and 2 BPRS unefficient. In fourth quarter there were 4 BPRS efficient. during the periode of 2015 (Quarter I - Quarter IV) there were 2 BPRS always efficient. Keyword : DEA, Islamic Rural Bank (BPRS), Efficiency, Input oriented